Bike Lock System Notification - ILMI NABIHAH NAZURAH BINTI ABDUL AZIZ,; NURUL AZMA BINTI ABDULLAH, (Applied Information Technology And Computer Science, 2025)
Bicycle theft in university is a major issue, caused by students' poor locking practices. Traditional bike locks are often not enough, and students frequently misplace keys or underestimate theft risks, resulting in the same cycle buying the same lock at a different price. This project proposes the development of a Bicycle Lock System Notification, which would convert traditional physical key locks into advanced, smartphone-operated locking devices integrated with secure bike parking. Using Arduino-based microcontrollers, this system aims to improve bike security, with lower costs, and organize parking. Notifications play a crucial role by alerting users in real-time about any unauthorized attempts to access their bicycles, providing an additional layer of security. The project uses a prototyping methodology to ensure functionality and performance. The proposed solution provides a modern, cost-effective, and organized approach to bicycle security on university area, addressing current problems while improving overall safety and convenience for student cyclists.